MENJAWAB PEMBENTUKAN AUKUS DI KAWASAN ASIA PASIFIK MENGGUNAKAN PRINSIP BEBAS AKTIF INDONESIA - Azzqy, Andrea Abdul Rahman; Awal, Syahrul (Universitas Jenderal Ahmad Yani, 2023)
The formation of the AUKUS alliance by the United States, Britain, and Australia in September 2021 concerns Indonesia in maintaining stability and security in the Asia Pacific region. As a key player, Indonesia responded to AUKUS with the principle of